Vocabulary Learning Strategies Using By Students’ During Covid-19 Pandemic - Rera, Ega Prasetya; Qalyubi, Imam; Qamariah, Zaitun (PT. Marosk Zada Cemerlang, 2023)
The purpose of this study is to describe strategies for mastering English, the main thing that usually has to be mastered is Vocabulary. This type of research is a qualitative approach. Data obtained from observation, interviews and documentation. The subjects of this study were second semester students of the English study program at IAIN Palangka Raya. Then, the object of this research is learning strategies and also factors that contribute in increasing the vocabulary used by English students. They were selected by purposive sampling technique. Interviews were used to determine learning strategies and contributing factors in increasing students' vocabulary. The findings of this study indicate the following points: (1) students use strategies to increase vocabulary, especially during the Pandemic. The strategies include: direct strategies, namely memory strategies, cognitive strategies and compensation strategies. While the indirect strategies are metacognitive, affective strategies and social strategies. Although there are several strategies in learning, here the informants only use cognitive, memory, and metacognitive strategies. Each student has a different strategy that is tailored to their own desires. This strategy is very helpful for students because they can adapt it to their preferred way of learning. (2) in increasing students' vocabulary, there are also contributing factors. The chosen factor is also the same as choosing a learning strategy, because this factor also has a role that is almost the same as the strategy. These factors are usually used when they are studying, namely when they have free time so that even though they are relaxed, they can still get vocabulary.